Gape Angle in Asymptomatic Dogs with Normal Occlusion. (March 2021) - Thomson, Amy; Hetzel, Scott; Snyder, Christopher J.
This study reports the gape angle (vertical temporomandibular joint range of motion for mouth opening) in conscious and anesthetized dogs. Mouth opening was reported as an angle in this study. Additionally, conscious and anesthetized measurements were compared to see if the state of anesthesia affected this measurement in asymptomatic patients. This prospective study evaluated 165 anesthetized dogs. Patients were placed in 1 of 2 groups: dental patients or non-dental patients. Only patients who were reported by owners to be asymptomatic for oral pain were included in the study. All dogs that met inclusion criteria had the maxillary length and interincisal distance measured. There was no difference (p = 0.590) between the mean (+/-SD) gape angle of conscious 44.0 o (+/- 4.1+ o ) and anesthetized patients 43.9 o (+/- 3.9 o ). No difference was seen in the gape angle between dental (44.2 o ) and non-dental patients (43.2 o ) (p = 0.183), or between conscious (43.8 o ) and anesthetized patients (43.7 o ) (p = 0.610). This study suggests that a consistent gape angle of 44 o exists in dogs not exhibiting overt signs of oral pain and the gape angle is easy to measure in conscious patients and may be a useful tool during routine physical examination to identify patients with restricted range of motion. Immediate clinical application of this information can be used to monitor progress of treated patients affected by disorders that cause a decreased gape angle.